In Situ Effects of a Microplastic Mixture on the Community Structure of Benthic Macroinvertebrates in a Freshwater Pond. (29th June 2021) - Stanković, Jelena; Milošević, Djuradj; Jovanović, Boris; Savić‐Zdravković, Dimitrija; Petrović, Ana; Raković, Maja; Stanković, Nikola; Stojković Piperac, Milica
Abstract: Benthic communities contain some of the most threatened organisms in aquatic habitats due to different anthropogenic pressures. The high abundance of microplastics in sediments will continue to increase in the future, further increasing the probability of interactions between macroinvertebrates and microplastics. In the present study, a benthic community in a relatively pristine shallow pond was exposed either to an environmentally relevant high concentration of a microplastic mixture of 80 g m –2 in the sediment, or a control sediment, without the addition of microplastics. The mixture of microplastics contained irregularly shaped polyethylene, polyvinyl chloride, and polyamide in a ratio of 50:25:25%, respectively. The in situ experiment lasted for 100 d. The total number of taxa that colonized the microcosms was 22 (17 in the control and 18 in the microplastic treatment), and the colonization was not affected by the treatment. The most dominant group within the macroinvertebrate community was the dipteran family Chironomidae, in both the control and the microplastic treatment. No significant differences in the abundance and biomass at a community level were recorded between the groups by permutational multivariate analysis of variance ( F  = 0.993, p  = 0.456 and F  = 0.344, p  = 0.797, respectively). The mixture of microplastics did not influence the abundance or biomass of the functional feeding groups ( F  = 1.810, p  = 0.137 and F  = 0.377, p  = 0.736, respectively). The species richness, species abundance, species biomass, Shannon's diversity index, and Simpson's index of diversity showed no statistically significant differences between the control and treatment groups. Czekanowski's quantitative similarity index indicated that 84% of the community remained unaffected after microplastic exposure. Environ Toxicol Chem 2022;41:888–895. © 2021 SETAC Abstract : Exposure of freshwater benthic macroinvertebrate community to a high concentration of a microplastic mixture of irregular shaped polyethylene (PE), polyvinylchloride (PVC), and polyamide (PA), with control on the right.